2021
DOI: 10.3389/fmars.2021.710973
|View full text |Cite
|
Sign up to set email alerts
|

Climate Signals in the Black Sea From a Multidecadal Eddy-Resolving Reanalysis

Abstract: Ocean reanalyses are becoming increasingly important to reconstruct and provide an overview of the ocean state from the past to the present-day. In this article, we present a Black Sea reanalysis covering the whole satellite altimetry era. In the scope of the Copernicus Marine Environment Monitoring Service, the Black Sea reanalysis system is produced using an advanced variational data assimilation method to combine the best available observations with a state-of-the-art ocean general circulation model. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…This could be related to the highest SST variability in 1994, as shown in the EOF analysis (Figure 4c,d). In addition, [2,26] found a warm peak in 1994 occurring in the second half of the year, confirming our results. Except for 1994, the temporal basin's average MHW duration (Figure 6c) shows a general increase from roughly 6 days to >10 days in the last decade (2010-2020), with a maximum of ~24 days in 2020.…”
Section: Relations Between Mhw and Ensosupporting
confidence: 90%
See 3 more Smart Citations
“…This could be related to the highest SST variability in 1994, as shown in the EOF analysis (Figure 4c,d). In addition, [2,26] found a warm peak in 1994 occurring in the second half of the year, confirming our results. Except for 1994, the temporal basin's average MHW duration (Figure 6c) shows a general increase from roughly 6 days to >10 days in the last decade (2010-2020), with a maximum of ~24 days in 2020.…”
Section: Relations Between Mhw and Ensosupporting
confidence: 90%
“…This event may be linked to the high variability observed in the EOF analysis (Figure 4c,d). This showed that the second half of 1994 had the highest variability over the entire study period, confirming prior research findings [2,26].…”
Section: The Longest Mhw Eventsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, the geostrophic currents estimated from the time-averaged sea level (1993-2019) reveal the Rim current, which surrounds the entire Black Sea and forms a large-scale cyclonic gyre (Figure 7). Major details are provided in [47].…”
Section: Validation Of Bs-phy Systemsmentioning
confidence: 99%